Symptomatic pulmonary embolus after catheter removal in children with catheter related thrombosis: A report from the CHAT Consortium - Jaffray, Julie; Baumann Kreuziger, Lisa; Branchford, Brian; Wee, Choo Phei; Faustino, E. Vincent S.; Zakai, Neil A.; Croteau, Stacy E.; Silvey, Michael; Fargo, John H.; Cooper, James D.; Bakeer, Nihal; Stillings, Amy; et al. (Journal of thrombosis and haemostasis, 2022)
Background Appropriate timing of central venous catheter (CVC) removal, in relation to start of anticoagulation, in children after the diagnosis of a CVC‐related thrombosis (CRT) is not well established. Objectives This retrospective cohort study evaluated the incidence of symptomatic pulmonary embolism (PE) after CVC removal using data from the multi‐institutional Children’s Hospital‐Acquired Thrombosis (CHAT) Consortium Registry. Patients/Methods The CHAT Registry consists of data from children aged 0–21 years with a hospital‐acquired venous thromboembolism. Eligible subjects were those with CRT diagnosed <3 days after CVC removal. Subjects were excluded if the CRT was due to a failed CVC insertion. Subjects were divided into three groups: those with CVC removal without anticoagulation, those with CVC removal <48 h after starting anticoagulation, and those with CVC removal ≥48 h after starting anticoagulation. Results A total of 687 CRT events from 663 subjects were included. A majority of CRT events were in subjects with peripherally inserted central catheters (62.3%, n = 428). For the 611 CRT events in which the CVC was removed, there was only one case of symptomatic PE (0.16%), which occurred <48 h after initiation of anticoagulation. Conclusions While current guidelines suggest anticoagulation before CVC removal in the setting of a CRT to prevent embolization, CVC removal is not associated with symptomatic PE regardless of duration of anticoagulation before CVC removal.